The Attitudes of Students Towards Cooperative Learning in ELT Classes - Sühendan Er; Bengü Aksu Ataç (Informascope, 2014)
In teaching and learning environments, many methods, techniques and/or approaches are used. Among these one of them is cooperative learning. It is defined as working in the soul of a team and in the team, the members help, motivate and trust each other. This study aimed at investigating the University prep school ELT students' attitudes towards cooperative learning.  A questionnaire was given to 166 (F=100, M=66) university students whose ages  were between 18-20 who were all studying at prep school and of different faculties. A questionnaire inquiring on the students' attitudes on cooperative learning was administered. The collected data was analyzed by using descriptive analysis method. Results showed that 66,9% of the students are at the side of cooperative learning in ELT classes whereas 33,1% of them believed that if they work alone they would have better results and they thought working alone was more enjoyable. A focus group was organized and the students mentioned both negative and positive sides of cooperative work. Furthermore, the findings reported that there was difference in gender in the attitudes towards cooperative learning for the good of females.